Análise e caracterização da gestão dos resíduos da construção civil no município de Ribeirão Preto-SP - Silva, Luiz Paulo da (Universidade Federal de São Carlos, 2017)
Nowadays, daily changes are taking place, a product of the technological era, which offers every day a tangle of information and which increasingly value the consumption, the enjoyment of many of the goods produced, in the face of all this, it is highlighted what to do with the waste produced by the modern era. In the construction industry, waste products such as mortar residues, brick remnants, paints, plastics and others are produced for the execution of the activities, which often have a bad impact on the environment. The National Environmental Council - CONAMA, in its resolution no. 307/2002 and later with its amendments, stipulates the implementation of a plan for the correct management of Civil Construction Waste. In this context, the main objective of this study was to study the situation of RCC in the city of Ribeirão Preto, determining the amount of waste generated, through two parameters; licensed areas and volume discarded in authorized places, obtaining a generation rate of 183.28 kg / m². In the same way, the composition of the buckets was analyzed and the unit mass of 0.79 t / m³ was calculated. The work sought to relate the values and obtained a generation per capita of 1.24 kg / hab x day. To determine the clandestine disposal situation, an inventory was carried out with the main disposal sites, thus providing information relevant to city hall, building contractors and other agents involved.
Analysis and characterization of the management of civil construction waste in the municipality of Ribeirão Preto-SP
Keywords: Construção civil; Resíduos sólidos; Gestão ambiental; Resolução Conama 307; Civil construction; Solid Waste; Environmental management; Conama Resolution 307; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL